Precarização do trabalho docente e terceirização no Instituto Federal do Triângulo Mineiro (IFTM): indícios localizados na contratação de professores substitutos de 2009 a 2023 - Souza, Wilian Santos de (2024)
The present study, part of the research line Work, Society, and Education, within the Graduate Program in Education at the Federal University of Uberlândia, aimed to analyze general indicators in the hiring process of substitute teachers at IFTM that may demonstrate the precariousness of teaching positions and characterize outsourcing. The specific objectives outlined for this research were: i) present reflections on education and work in the emancipatory process; ii) identify aspects of production standards and their relationship with precariousness and flexibility; iii) understand outsourcing, its characteristics and dimensions; iv) outline the administrative process involved in hiring substitute teachers; and finally, v) examine the context in which IFTM operates and the relationship between the hiring of substitute teachers and outsourcing. In order to achieve these objectives, concepts related to education and work, as well as flexibility and outsourcing, were used along with methodological approaches associated with the hypothetical-deductive method in exploratory, descriptive, and documentary qualitative research. We hypothesized that indicators in the hiring of substitute teachers at IFTM demonstrate the precariousness of teaching positions and characterize the outsourcing of core activities in public administration. When analyzing this proposition, we concluded that from a formal legal point of view, this is not outsourcing. However, it was possible to demonstrate from the data and theoretical basis that, in fact, from a practical perspective, from real and concrete life, the activity of substitute teachers meets all the conditions and characteristics of an outsourcing of the core activity.